The magnitude of the infection for the HIV-Aids in greaters of 50 years in the city of Fortaleza-CE - Feitoza, Aline R.; Souza, Adriano R.; Araújo, Maria Fátima M. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: now has been noticing if changes in the course of the epidemic of the aids, and one of them is the increase of the number of cases inthe age group from 50 to 70 years, the one that comes demonstrate the exclusion of this group in the projects and education programs and prevention of the HIV-aids. Objetive: this study has as objective characterizes the magnitude of the aids in larger of 50 years in the municipal district of Fortaleza-CE. Methods: it is treated of an epidemic study, where they were certain rates as to incidences, prevalence, lethality and potential years of life lost, through data picked in the System of Information and Offences you Notified (SINAN) referring to the period from 1991 to 2001. Results: being analyzed the magnitude of the aids, it was noticed that the disease in that specific population presents great epidemic relevance, not for theabsolute numbers, but for the incidence rates (7,65 cases p / 100.000), prevalence (224,9 p / 100.000 hab. in the masculine sex), lethality (43,9%) andpotential years of life lost (in up to 15 years). Conclusion: this study revealed the magnitude of the epidemic, strengthening the knowledge producedas significant for the understanding of the aids as problem of Public Health, that includes people with superior age to 50 years, therefore opening newperspectives in the field of that epidemic.